Improvement of constructability guidelines for design phase in highway project / Siti Hafizan Hassan, Nadira Ahzahar and Hazrina Ahmad - Hassan, Siti Hafizan; Ahzahar, Nadira; Ahmad, Hazrina (2009)
Government and private agencies that carried out highway construction project arc facing the reality that the public will no longer tolerate construction projects that arc insensitive to road users and adjacent communities. According to Russell cl al. (1993), highway construction projects are characterized by traffic problems, changes of design, poor planning, disputes, cost overruns, poor safety practices and time delays. Constructability is seen as one of the best solutions to these problems where it has demonstrated the potential to minimize the number and magnitude of chances, disputes, cost overruns, and delays during construction. Conslructabilitv has been defined in a number of ways. Constructability is described as the optimum use ol construction knowledge and experience in planning, desicn. procurement, and held operations to achieve overall pioject objectives